การเฝ้าสังเกตการกัดกร่อนเชิงความเค้นของวัสดุที่ใช้ทำภาชนะรับความดันโดยวิธีการปล่อยคลื่นอะคูสติก - สินชัย บริบูรณ์สกุลสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
In order to test the feasibility of using acoustic (AE) technique for detection and monitoring of stress corrosion cracking on 304 austenitic stainless steel. The residual stress from a bending specimens and 0.35 M sodium chloride solution that was acidified to pH 2.34 at room temperature induced stress corrosion cracking. The AE signals that were measured by piezoelectric sensor. The results showed that AE signals were easily detected during stress corrosion and a good correlation was observed between AE activity and corrosion evolution. The determination of the source location of each event can detected by used two sensors to detect AE signal simultaneous in difference distance, the corrosion position could be calculate from the difference time arrivals, position of sensors, and wave velocity of the sample. This method is work only pipes line testing but it does not provide sufficient information to locate the event in metal plate, however by using three sensors to as multi-sensor arrays and generate the hyperbola equation. The intersection of the three hyperbolas indicates the location of the event. Results from the pencil lead break testing (ASTM E-97) and HCI acid drop testing show that both methods can use to determine the source location with error 5%